1991
DOI: 10.1002/j.1460-2075.1991.tb07755.x
|View full text |Cite
|
Sign up to set email alerts
|

The path of mRNA through the Escherichia coli ribosome; site-directed cross-linking of mRNA analogues carrying a photo-reactive label at various points 3′ to the decoding site.

Abstract: mRNA analogues approximately 40 bases long were prepared by T7 transcription from synthetic DNA templates. Each message contained the sequence ACC‐GCG (coding for threonine and alanine, respectively), together with a single thio‐U residue located at a variable position on the 3′‐side of these coding triplets. The thio‐U residue was either substituted with 4‐azidophenacyl bromide to introduce a photo‐reactive group, or was left unsubstituted for direct UV cross‐linking. After binding to Escherichia coli 70S rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…It is noteworthy that the main mRNA crosslinking target on the 16S RNA identified in this paper is compatible with one of the two positions (i.e. nucleotide 532) found covalently linked to the mRNA by RinkeAppel et al [16]; however° other regions of the 16S RNA (i.e. position 1050 [24], 1390-1400 [16,25,26] and the Y-terminus [24,26]) which have been implicated in mRNA-ribosome interaction in other studies were found to be crosslinked to the mRNA either very weakly or not at all (spot 11 of Fig.…”
Section: 'supporting
confidence: 89%
See 3 more Smart Citations
“…It is noteworthy that the main mRNA crosslinking target on the 16S RNA identified in this paper is compatible with one of the two positions (i.e. nucleotide 532) found covalently linked to the mRNA by RinkeAppel et al [16]; however° other regions of the 16S RNA (i.e. position 1050 [24], 1390-1400 [16,25,26] and the Y-terminus [24,26]) which have been implicated in mRNA-ribosome interaction in other studies were found to be crosslinked to the mRNA either very weakly or not at all (spot 11 of Fig.…”
Section: 'supporting
confidence: 89%
“…Based on our current knowledge, in this rRNA region, the 530 loop is the most likely candidate for an interaction with the mRNA. In fact, this universally conserved segment of the 16S RNA constitutes a functional pseudoknot [1(3] implicated in and probably stabilized by protein S12 binding [11,i2], involved in A-site decoding [13], streptomycin sensitivity [14o15], mRNA binding [16] and possibly in monitoring translational reading frame [17]. Furthermore, based on a number of considerations summarized by Brimacomb¢ [18], it is now suggested that the methylated G at position 527, which belongs to the 530 loop region, is in a tight cluster with almost all other modified bases of the rRNA.…”
Section: 'mentioning
confidence: 99%
See 2 more Smart Citations
“…The 50S subunits reconstituted from the four fragmented 23S rRNA species carrying 32 P-labeled psUp at the cleavage sites were separated by sucrose gradient centrifugation and subjected to mild UV irradiation at 350 nm (Rinke-Appel et al+, 1991; Dontsova et al+, 1992)+ The rRNA was then isolated from the irradiated subunits (or from nonirradiated control subunits) by phenol extraction, and the crosslinked regions within the rRNA were localized using the RNase H (Dontsova et al+, 1991;Rinke-Appel et al+, 1991)+ For this purpose, either two or three oligodeoxynucleotides (10-20 nt long) complementary to the 23S rRNA were necessary in the RNase H digestions+ The first oligodeoxynucleotide is complementary to a region upstream of the psUp site, so as to release a short rRNA fragment carrying the 32 P-labeled psUp residue+ This oligodeoxynucleotide is kept constant in the RNase H digestions, whereas the second one (and the third one, if present) is varied so as to excise different sections of the 23S rRNA encompassing the crosslinked target site (or sites)+ In contrast to the digestions with the chimeric oligonucleotides used to generate the initial specific cuts in the rRNA, these RNAse H digestions are performed at 558 with an excess of enzyme (cf+ RinkeAppel et al+, 1991)+ Candidates for the "constant" oligodeoxynucleotide were carefully selected so as to obtain a clean and quantitative digestion in every case+ Thus, in the subsequent gel electrophoresis of the rRNA fragments released by the RNase H, the lanes from the control (nonirradiated) 50S subunits should only show the short fragment carrying the labeled psUp in each case, whereas the lanes from the irradiated subunits should, in addition, show products corresponding to this short fragment crosslinked to the fragments of variable length excised from the target region+ Examples of these gels are illustrated in Figure 3, and will be described below for the individual crosslinks+ When the locations of the crosslink sites had been narrowed down in this way to rRNA regions of less than ca+ 50 nt, the sites of crosslinking within the regions concerned were analyzed by primer extension (Moazed et al+, 1986)+ The substrates for the primer extension reactions were isolated from RNase H digestions on a preparative scale+ For this purpose, the digestions were chosen so as to release the crosslinked material as a relatively large rRNA complex of 100-200 nt (cf+ Fig+ 3A, lane 5, or Fig+ 3B, lane 1), and a control fragment was extracted from the same gel lane in each case+ These control fragments represent the noncrosslinked rRNA from the target region and do not contain the region with the radioactive psUp residue; they could accordingly be located by UV shadowing as bands moving just below the corresponding crosslinked complexes in the gels+ Examples of the primer extension gels obtained from the crosslinked and control fragments in the various cases are shown in Figure 4, and are described below for the individual crosslinks+ As a result of the artifacts that are often observed in primer extension analyses of crosslink sites (see Brimacombe, 1995, for discussion), we only consider a stop signal in the reverse transcriptase gels as being indicative of a crosslink site if it is reproducibly observed within the short rRNA region already defined by the RNase H digestions (cf+ Fig+ 3)+…”
Section: Crosslinking and Analysis Of Crosslink Sitesmentioning
confidence: 99%